Embedded Ethernet Web Server for a Robot Arm Control - Zaw, Toe Oo (2002)
The World Wide Web has provided a strong medium for networked computing with independent platform. As the Internet continues to grow, there will be a practical as well as economical sense to connect number of devices to the Internet. Hence, embedded web servers are needed to access, monitor, and control these devices. This work investigates the issues involved in developing an embedded web server which monitors and controls a number of devices through its re-configurable I/O ports. This thesis also provides detail discussion on the software and hardware aspects of an embedded web server. Site Player embedded server module is used as a base unit in this research. With the PC interface, embedded server module is configured with appropriate I/O control codes as well as user interface. The example application used with the embedded server module is a servodrive robot arm which has four servo motors to control the movements of its base, arm, wrist, and grip. Further integration and greater capability of web-enable devices which are being used in factory automation and home appliances control are discussed as future works of this research.